Introduction d’un nouveau protagoniste dans le récit en français et en chinois : interaction des structures syntaxique et informationnelle - Arnaud Arslangul (Discours)
The referential introduction in narrative discourse is influenced by different factors. This study focuses on the interaction between syntactic and informational levels in structuring the utterance when introducing a new protagonist into narratives. The aim is to identify which constructions are used to encode this introductory function in French and Chinese. The procedure used consists of the analysis of an oral corpus collected from native speakers of these two languages. The stimulus used is a cartoon composed of ten plates of four drawings. It presents a narrative quest in which the main character meets other protagonists. The results show that the two groups of speakers use different strategies to locate these new referents in the story. French speakers, using the canonical predicative construction, rely on the temporal reference to integrate the appearance of new protagonists to other events in the chronology of the story. Chinese speakers, using the monoclausal presentational construction, pay particular attention to the spatial reference which serves to establish discursive coherence between the utterances.